Feasibility Study of Rooftop Grid Connected PV System for Peak Load Reduction - Syafii Syafii; Novizon Novizon; Wati Wati; Dona Juliandri (IAES Indonesia Section, 2018)
This paper presented the economic feasibility analysis of grid-connected photovoltaic on the roof of building, to reduce peak electrical demand. The Engineering Faculty electrical system is used as case study of PV system economic feasibility. The economic calculation assumptions used are: electricity tariff IDR 1114.74 per kWh based on electricity tariff for medium voltage load, estimated annual module degradation 0.5% and the life expectancy of the solar panels 25 years. The interest rate using of Bank Indonesia (BI) rate for 2018 i.e. 4.25% and inflation rate 3% also considered. The initial investment required to build 117.5 kWp PV system is IDR 2,413 million. The operational and maintenance costs are estimated 1% of initial investment per year. The result of cash flow rate shows that a positive NPV is achievable and payback period less then solar panels life expectancy. The simple payback period is 11 years and discounted payback period calculated by consider multiple parameters to be 14 years. The result of economic analysis using current rate value indicate that the project is profitable.